Studi Kasus: Persepsi Warga Binaan Pemasyarakatan Laki-laki Indonesia tentang COVID-19 - Handayaningtyas, Ayu Dita; Andriany, Megah; Ediati, Annastasia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
The prevalence of Corona Virus Disease 2019 (COVID-19) in correctional facility has increased. Analysis of the handling of COVID-19 during the pandemic has never explored the perceptions of prisoners in prisons in Indonesia and it is important to know the perspective of prisoners in prisons. This research has never been conducted in Indonesia. The aim of this research is to describe the perceptions of male prisoners towards COVID-19 in correctional institutions in Indonesia. The design used by researchers is a case study. Data collection was carried out by in-depth interviews with five male inmates at Correctional Institution of Ambarawa Class IIA. The data analysis used is the Collaizi interpretation method. The results show that prisoners perceive it as normal and there are also prisoners who are worried if they contract COVID, prisoners also have attitudes and behaviors that support self-care in carrying out the COVID-19 health protocol. The conclusion of this case study is that prisoners during the COVID-19 outbreak followed officers' directions to comply with health protocols and obtain COVID-19 information from the media and officers